2012
DOI: 10.1021/am301389u
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Colored Passive Layers on Zirconium: Morphology, Optical Properties, and Corrosion Resistance

Abstract: Brightly colored and uniform passive layers on Zr can be formed by applying alternating current (ac) voltage (V(ac)) for 10 s in 10 wt % aqueous Na(2)SO(4) solution at T = 298 K. The coloration originating from iridescence can be fine-tuned by adjusting V(ac) in the 10-80 V range. Visible light microscopy analysis shows that different grains reveal two or three different colors due to the polycrystalline nature of Zr, and the resultant coloration is the sum of these contributions. Reflectance spectroscopy spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(32 citation statements)
references
References 31 publications
5
26
0
Order By: Relevance
“…Wire electrodes were then treated in the etching solution described above, rinsed with UHP water, and sonicated in an ultrasonic bath (Branson) for 1 min. All Ti electrodes were immersed in a single compartment electrochemical cell where the electrochemical coloration was carried out by application of AC voltage ( V AC ). , A counter electrode of Pt foil spot-welded to a Pt wire (Johnson-Matthey, 99.9 wt %) was employed; with a real surface area of a minimum 10 times greater than that of the Ti electrode. The distance between the working (Ti) and counter (Pt) electrodes was maintained at ca.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wire electrodes were then treated in the etching solution described above, rinsed with UHP water, and sonicated in an ultrasonic bath (Branson) for 1 min. All Ti electrodes were immersed in a single compartment electrochemical cell where the electrochemical coloration was carried out by application of AC voltage ( V AC ). , A counter electrode of Pt foil spot-welded to a Pt wire (Johnson-Matthey, 99.9 wt %) was employed; with a real surface area of a minimum 10 times greater than that of the Ti electrode. The distance between the working (Ti) and counter (Pt) electrodes was maintained at ca.…”
Section: Methodsmentioning
confidence: 99%
“…We previously published an extensive study on the electrochemical passivation of Zr and the resulting properties achieved . Although Ti and Zr possess many similar properties, they still reveal certain differences, such as grain structure and size, that are of particular relevance to this research.…”
Section: Introductionmentioning
confidence: 99%
“…Results from SEM-EDXRF showed that stellite 6 particles penetrate into the copper plates and mechanical tests indicated that this process increased hardness of the material. Holmberg et al 37 characterized the brightly coloured uniform passive layers formed on zirconium by electrochemical treatments using many different methods. Prolometry and AFS were used to examine the surface roughness and surface morphology.…”
Section: Non-ferrous Metalsmentioning
confidence: 99%
“…Self-colored films can be grown on many metal substrates such as titanium, steel, niobium, tantalum, and zirconium. 5 Recently, there have been many methods used in coloring various metals such as electrochemical techniques 6,7 and magnetic sputtering methods, 8,9 etc. However, the magnetron sputtering technique is a dominant method of syntheses of thin films which is extensively used at laboratory or industrial scales for the preparation of various types of single or multioxides or other oxide-based composite layers.…”
Section: ■ Introductionmentioning
confidence: 99%